Exploring evaluator role and identity - Ryan, Katherine E.; Schwandt, Thomas A. (Evaluation and society., 2002)
An exploration of evaluator role and identity. The areas addressed include: evaluation in an organizational world; evaluation as responsibility, conscience and conviction; the evaluator's role in the transformative context; hidden images of self; and evaluation in dystopian times.